Changes in the population and diversity of plant parasitic nematodes and their effects on sugarcane growth at Wonji‐Shoa Sugar Estate, Ethiopia - Alemayehu Dengia; Nigussae Dechassa; Lemma Wogi; Berhanu Amsalu (Agrosystems, Geosciences & Environment)
Abstract In Wonji‐Shoa Sugar Estate (WSSE), sugarcane (Saccharum spp. hybrid) yields have declined by about 48% over the last 70 years. One of the causes for the decline is assumed to be the long‐term monoculture production system that results in the buildup of plant parasitic nematodes (PPNs). Therefore, the population and diversity of PPNs were investigated by conducting soil sampling using a biosequential method (simultaneous sampling of the soils of adjacent cultivated land [CL] and uncultivated land [UL]) and a chronosequential method (taking soil samples at different times from the same site). The samples were subjected to analysis using standard procedures to determine the change in the population, and identify the genera of PPNs. Additionally, a pot experiment that involved fumigation was conducted on top soils sampled from the CL and UL of the plantation. The results revealed that about 10 genera of PPNs (Meloidogyne, Helicotylenchus, Hoplolaimus, Rotylenchulus, Hemicycliophora, Discriconemella, Xhiphinema, Pratylenchus, Tylenchorhynchus, and Scutellonema) were detected, of which the first four were newly identified. The population density and the number of genera of PPNs found in the CL were 36‐fold and 4.5‐fold higher than those found in the UL, respectively. Furthermore, fumigation reduced the population of the PPNs by 61% and increased production of cane biomass by 63%. It is concluded that the soils of the WSSE are infested by PPNs, which consequently have detrimental effects on sugarcane growth. While amending soil fertility is crucial, reversing the decline in sugarcane yields also necessitates implementing an integrated soil management system that includes PPNs.